2018
DOI: 10.1186/s12992-018-0344-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sugar and processed food imports on the prevalence of overweight and obesity in 172 countries

Abstract: BackgroundStudies find that economic, political, and social globalization – as well as trade liberalization specifically – influence the prevalence of overweight and obesity in countries through increasing the availability and affordability of unhealthful food. However, what are the mechanisms that connect globalization, trade liberalization, and rising average body mass index (BMI)? We suggest that the various sub-components of globalization interact, leading individuals in countries that experience higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…The reasons for exclusion were that two articles were not directly related to economic globalization, two articles did not report any outcome pertaining to body weight status, four articles were narrative review, commentary, or study protocol instead of original study, and the other six articles were not data‐driven empirical research. In total, 16 articles met the eligibility criteria and were included in the review …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for exclusion were that two articles were not directly related to economic globalization, two articles did not report any outcome pertaining to body weight status, four articles were narrative review, commentary, or study protocol instead of original study, and the other six articles were not data‐driven empirical research. In total, 16 articles met the eligibility criteria and were included in the review …”
Section: Resultsmentioning
confidence: 99%
“…Miljkovic et al reported a positive association between foreign direct investment and obesity among less‐developed countries. Lin et al documented sugar and processed food imports to be positively associated with mean BMI. Barlow et al found that the Canada‐US Free Trade Agreement was associated with a substantial rise in calorie availability in Canada.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In ecological globalization, which reflects that country is more depending on products from the outside world because of limited space left to produce food. Imported food which usually comes as processed food and not fresh causes health issues like obesity (Lin et al 2018).…”
Section: Discussionmentioning
confidence: 99%